LAUNCHING STALISM IN BULGARIA - Marinova, Mina (Revista Inclusiones, 2020)
After the Second World War the communist doctrine and the experience of the USSR offered eastern European countries a detailed matrix for imposing political and social-and-economic changes. With the beginning of the Cold War the processes of Sovietization and imposition of Stalinism in the satellite countries were sharply accelerated. In 1949 a decisive battle for supremacy took place in the Bulgarian communist party. It was won by those communists who had come back from Moscow after the WWII. Under the directions of Stalin and with the presence of his advisers and troops was established a regime that was not simply obedient but was built up by strict adherence to the soviet model and was meant to ensure the direct control of Moscow.